Effectiveness of Health Services in controlling the Increase in the Number of Hypertension Suffering Cases in Community Health Centers Sangurara Palu - Arif, Renny Febrina; Joko prasetyo (Universitas STRADA Indonesia, 2024)
Efforts to control non-communicable diseases, especially hypertension as one of the diseases with the greatest prevalence in Indonesia, need to be of concern to the government and health workers in public health services. Managing health service management is one way to control hypertension cases in society. This community service program was carried out by first carrying out a preliminary study as an initial stage of activities to formulate problems and determine priority issues related to controlling hypertension cases at the Sangurara Palu Community Health Center. In this program, several activities are carried out that can support the successful control of hypertension cases, such as education and outreach regarding the prevention, treatment and care of hypertension. From the implementation of activities to overcome the problem of the effectiveness of controlling hypertension cases, it can be used as input for the Sangurara Community Health Center in the management of community health center management related to the number of hypertension cases.